Neurosteroid [3α,5α]-3-hydroxy-pregnan-20-one enhances IL-10 production via endosomal TRIF-dependent TLR4 signaling pathway - Balan, Irina; Grusca, Adelina; O’Buckley, Todd K.; Morrow, A. Leslie (Frontiers in Endocrinology, 2023)
Background Previous studies demonstrated the inhibitory effect of allopregnanolone (3α,5α-THP) on the activation of inflammatory toll-like receptor 4 (TLR4) signals in RAW264.7 macrophages and the brains of selectively bred alcohol-preferring (P) rats. In the current study, we investigated the impact of 3α,5α-THP on the levels of IL-10 and activation of the TRIF-dependent endosomal TLR4 pathway. Methods The amygdala and nucleus accumbens (NAc) of P rats, which exhibit innately activated TLR4 pathways as well as RAW264.7 cells, were used. Enzyme-linked immunosorbent assays (ELISA) and immunoblotting assays were used to ascertain the effects of 3α,5α-THP on the TRIF-dependent endosomal TLR4 pathway and endosomes were isolated to examine translocation of TLR4 and TRIF. Additionally, we investigated the effects of 3α,5α-THP and 3α,5α-THDOC (0.1, 0.3, and 1.0 µM) on the levels of IL-10 in RAW264.7 macrophages. Finally, we examined whether inhibiting TRIF (using TRIF siRNA) in RAW264.7 cells altered the levels of IL-10. Results 3α,5α-THP administration facilitated activation of the endosomal TRIF-dependent TLR4 pathway in males, but not female P rats. 3α,5α-THP increased IL-10 levels (+13.2 ± 6.5%) and BDNF levels (+21.1 ± 11.5%) in the male amygdala. These effects were associated with increases in pTRAM (+86.4 ± 28.4%), SP1 (+122.2 ± 74.9%), and PI(3)K-p110δ (+61.6 ± 21.6%), and a reduction of TIRAP (−13.7 ± 6.0%), indicating the activation of the endosomal TRIF-dependent TLR4 signaling pathway. Comparable effects were observed in NAc of these animals. Furthermore, 3α,5α-THP enhanced the accumulation of TLR4 (+43.9 ± 11.3%) and TRIF (+64.8 ± 32.8%) in endosomes, with no significant effect on TLR3 accumulation. Additionally, 3α,5α-THP facilitated the transition from early endosomes to late endosomes (increasing Rab7 levels: +35.8 ± 18.4%). In RAW264.7 cells, imiquimod (30 µg/mL) reduced IL-10 while 3α,5α-THP and 3α,5α-THDOC (0.1, 0.3, and 1.0 µM) restored IL-10 levels. To determine the role of the TRIF-dependent TLR4 signaling pathway in IL-10 production, the downregulation of TRIF (−62.9 ± 28.2%) in RAW264.7 cells led to a reduction in IL-10 levels (−42.3 ± 8.4%). TRIF (−62.9 ± 28.2%) in RAW264.7 cells led to a reduction in IL-10 levels (−42.3 ± 8.4%) and 3α,5α-THP (1.0 µM) no longer restored the reduced IL-10 levels. Conclusion The results demonstrate 3α,5α-THP enhancement of the endosomal TLR4-TRIF anti-inflammatory signals and elevations of IL-10 in male P rat brain that were not detected in female P rat brain. These effects hold significant implications for controlling inflammatory responses in both the brain and peripheral immune cells.